Students’ Perception toward The Use of Podcasts in Learning Listening at Mts Unggulan Al Kautsar Trowulan Mojokerto - Rinda Rinda (Language-Edu, 2020)
Podcast is considered as a component of ICT (Information and Communication Technology) that has been broadly utilized and demonstrated as a compelling apparatus in instructing English. Covid-19 has been announced as a worldwide pandemic by WHO. Subsequently, this examination was utilized to explore the understudies' observation towards the utilization of web recording in getting the hang of tuning in. This study employs survey Method, In addition, this survey is followed up with interviews for more in-depth data. The involvement of both data from survey and those from interviews is to obtain more dependable information concerning the topic investigated. This study involved fifteen students as the research participants to respond to questionnaire. Furthermore this study followed up the result of questionnaire by interviewing 3 out of those 15 participants. To collect the data questionnaire was distribute use Googleform media with multiple-choice items, and Whatsahapp media to collect interview data. The discoveries uncover that the understudies had positive discernments towards podcasts. The vast majority of the members concurred that they like podcasts since it helped them in learning English especially listening ability. Another positive effect was that the students’ vocabulary improved. Hence, the findings suggest that podcast can be used as the alternative teaching media to improve students’ listening skills.